Tinjauan Hukum Ekonomi Syariah Terhadap Kebijakan Program Penghapusan Utang UMKM - Syifa Salsa Bila; Listian Indriyani Achmad; MH Ainulyaqin; Sukron Mamun; Yudianto Achmad (Jurnal Ilmiah Ekonomi Islam, 2026)
The MSME debt crisis that occurred after the pandemic caused systemic credit congestion and hampered national economic growth. The objective is to examine the policy of repealing PP No. 47 of 2024 from the perspective of Islamic Business Ethics. The goal is to show how the policy can consider the humanitarian aspects of debtors facing problems with the principles of fairness and stability of the banking financial system. This research is a qualitative study using a literature review approach. The data collection technique used in this study is to record or cite information from various literature sources, including books, journals, documents, and other data and information sources relevant to the research topic. The results of the study show that PP No. 47/2024 provides a legal basis for HIMBARA banks to write off debts for the strategic sector of up to a maximum of IDR 500 million. This policy is in line with the principles of Inzar al-Mu'sir (relief for those facing difficulties) and Ibra' in Islamic Business Ethics. The government applies an ethical filter with a five-year waiting period to prevent moral hazard and ensure fairness. The use of Maslahah Mursalah, which prioritizes public interest and protection of property, is at the core of the MSME debt write-off policy (Hifdz al-Maal). This step is proof of the state's concern for the little people without neglecting the aspect of banking integrity, according to Islamic Business Ethics. To provide targeted assistance to debtors who are truly in need, not those who are deliberately negligent, its success is highly dependent on strict data monitoring and validation.